INVESTIGATION OF INTERACTION OF SODIUM LAURYL ETHOXY SULFATE AND ȮH RADICALS OBTAINED FROM INSOLUBLE PEROXO SOLVATES (Proceedings of the YSU B: Chemical and Biological Sciences, 2013)
Reaction ability of sodium lauryl ethoxy sulfate and ȮH radicals obtained from UV radiation of water solutions of ZnO·0.8H2O2, MgO·0.42H2O2 and CaCO3·0.21H2O2 peroxo solvates has been investigated. Substance oxidation by ȮH radicals was carried out by concurrent oxidation reaction method. To determine the hydrogen peroxides amount in peroxo solvates, permanganatometric method has been employed. Electron spectroscopy method has been carried out for determination of optical density. The results show, that obtained peroxo solvates accelerate the reaction between 4,4-dimethyl-4-nitrosoaniline (PNDMA) and ȮH radicals. The rate of constants of the reaction was obtained.
Keywords: peroxo solvates; discoloration reaction; UV radiation; ȮH radicals; PNDMA